The Externalities of Immigration Policies on Migration Flows: The Case of an Asylum Policy - Lucas Guichard; Joël Machado (Institute of Labor Economics (IZA), 2024)
We analyze the externalities arising from a bilateral asylum policy - the list of safe origin countries - relying on a tractable model. Using self-collected monthly data, we estimate that including one origin country on the safe list of a given destination decreases asylum applications from that origin to that destination by 29%. We use a counterfactual policy simulation to quantify the spillover effects occurring across origin and destination countries. Individuals from targeted origin countries move to alternative destinations. Individuals from untargeted origins divert from alternative destinations. The magnitude of the externalities depends on the size of the affected flows.
Keywords: F22; K37; J61; 330; migration; asylum seekers; asylum policy; safe origin country; refugee